Efeitos de audiências punitivas e não-punitivas do contexto educacional na acurácia do relato verbal de crianças - Furtado, Pedro Alves (Universidade Federal de São Carlos, 2024)
The present study evaluated the effects of two types of audiences (punitive educational agent and non-punitive educational agent), whose discriminative functions were established by verbal descriptions, on the accuracy of children's reports about their performances in a computerized game. Participants were two seven-year-old children who participated in a game where they were required to shoot at targets and then report on their performances during and at the end of each session. Baseline sessions evaluated the accuracy of participant’s reports in the presence of a neutral audience (Experimenter). Then, the discriminative functions of two audiences (punitive educational agent and non-punitive educational agent) were established by verbal descriptions. Participants were then exposed, in a alternated treatment design, to the punitive and non-punitive audience conditions to evaluate the effects of each type of audience on the accuracy of participant’s reports. Before each session, a Likert scale was presented to the participants to assess the function of the audiences. Both children showed an increase in the number of corresponding reports of errors when exposed to the non-punitive audience condition in comparison to the baseline (control) and punitive audience condition. Furthermore, the two participants emitted only non-corresponding reports about the total score at the end of the session for the punitive audience. When the audience was non-punitive or in the control condition (Experimenter), reports about the total score were accurate. Results suggest that different educational context audiences can control different reporting patterns, with the non-punitive audience producing an increase in correspondence and the punitive audience a decreasing in report accuracy, especially when the report was made directly to the audience. It’s discussed that educational agents whose goals were to obtain accurate reports on children’s performance should establish reinforcing contingencies for error or low-performance reports.
Effects of punitive and non-punitive audiences from the educational context on the accuracy of children's verbal reports
Keywords: Audiência; Agentes educativos; Comportamento verbal; Correspondência fazer-dizer; Crianças; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL::PROCESSOS DE APRENDIZAGEM, MEMORIA E MOTIVACAO